Characteristic and taste test of aromatherapy candle from essential oil of Cananga odorata - Kumalasari, Desy; Husnayanti, Ana; Pratiwi, Auronita Puspa (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Kenanga or ylang-ylang (Cananga odorata) is renowned in the pharmaceutical domain for its essential oil, which boasts therapeutic properties. This study aims to investigate the feasibility of utilizing C. odorata essential oil in the production of aromatherapy candles. It focuses on examining the oil’s characteristics, candle properties, and consumer preferences. The oil extraction employed the enfleurage method, while purification was achieved using a rotary evaporator. We adhered to the SNI 06-3949-1995 standards for analyzing the essential oil and the resultant candle characteristics. Consumer preferences were evaluated through surveys conducted with 30 panelists. The study’s results revealed an oil yield of 48.5%, consistent with the established standards. Optimally, the formula with 25% essential oil concentration demonstrated superior performance in aromatherapy candles, exhibiting a burn time of 8 hours, 30 minutes, and 30 seconds, and a melting point ranging from 51°C to 53°C. This concentration also elicited positive responses from participants in terms of the candles' appearance, aroma (both before and after burning), and therapeutic impact. Notably, the candles with a 25% essential oil concentration were most effective in rapidly delivering therapeutic benefits, predominantly inducing relaxation. The study concludes that ylang-ylang essential oil is highly promising for aromatherapy candle production, with the 25% concentration formula demonstrating optimal results in terms of standard compliance, burn time, and user satisfaction.